Computational analysis and expression profiling of potassium transport-related gene families in mango (Mangifera indica) indicate their role in stress response and fruit development - Lin Tan; Muhammad Waqas; Abdul Rehman; Muhammad Abdul Rehman Rashid; Sajid Fiaz; Hamid Manzoor; Farrukh Azeem (Frontiers in Plant Science, 2023)
Mango (Mangifera indica) fruit is known for its taste, health benefits, and drought tolerance. Potassium (K+) is one of the most abundant ions in a plant cell. It is important for various biological functions related to plant growth, development, and flowering/fruiting. It significantly contributes to fruit yield, quality, and drought tolerance in plants. However, molecular mechanisms comprising K+ transport in mango are least known. In the present study, 37 members of K+ transport-related genes (PTGs) were identified in mango, which include 22 K+ transporters (16 HAKs, 1 HKT, and 6 KEAs) and 15 K+ channels (6 TPKs and 8 Shakers). All PTGs were predicted to be expressed at the plasma membrane and possess characteristic motifs and domains. Phylogenetic analysis identified a strong kinship of PTGs among Oryza sativa, Arabidopsis thaliana, Cicer arietinum, Malus domestica, and M. indica. The promoter analysis identified 60 types of cis-elements related to various biological processes. RNA-seq-based expression profiling identified that MiTPK1.2, MiHAK1, MiHAK2.1, HAK6.1, and MiAKT1.1 were most upregulated in roots and that MiKEA2, MiAKT2, and MiAKT1 were upregulated in leaves. Moreover, MiAKT6, MiHAK1.1, MiKAT2, MiKAT2.1, MiHKT1, MiTPK1.1, MiHAK7, and MiHAK12 were highly expressed during the five growth stages of mango fruit. The current study is the first comprehensive report on K+ transport system in tropical fruits. Therefore, it will provide the foundation knowledge for the functional characterization of K+ genes in mango and related plants.